Pengaruh Etos Pimpinan terhadap Motif Berprestasi Kerja Karyawan - Suherman, Maman (FIkom Unisba, 2008)
In order to gain the predicate of Good Corporate Government, some government bureaus have managed to run strategic moves. PT Telkom was among those whose ambitions was to be the best e-government organization. The success of such program was never easy because many factors contributed on such matters. One of crucial factors contributed for the creating a good exemplar of Good Corporate Government is the workforce group, especially on the workers ability for working. To implement a good working performance, PT Telkom created a corporate culture reflected some ideal values, i.e. Cleanliness, Transparency, and Professionalism. It was the role of leaders then to socialize the values. Leaders have responsibilities to motivate workers in his unit. Motivation derived from many sources: given materials, communication activity, financial/material rewards, and so on. This paper examinee how leader’s ethos could be very effective in influencing workers motivation. In order to do so, ethos concept is divided by three aspects: credibility, attraction, and power. Research results show that the influence of leader’s credibility toward motivation is insignificant. On the other hand, there is significant relationship between appeals and leader’s power toward workers/staff motivation.